Comparative analyses of Mikania (Asteraceae: Eupatorieae) plastomes and impact of data partitioning and inference methods on phylogenetic relationships - Verônica A. Thode (Nature Portfolio, 2021)
Abstract We assembled new plastomes of 19 species of Mikania and of Ageratina fastigiata, Litothamnus nitidus, and Stevia collina, all belonging to tribe Eupatorieae (Asteraceae). We analyzed the structure and content of the assembled plastomes and used the newly generated sequences to infer phylogenetic relationships and study the effects of different data partitions and inference methods on the topologies. Most phylogenetic studies with plastomes ignore that processes like recombination and biparental inheritance can occur in this organelle, using the whole genome as a single locus. Our study sought to compare this approach with multispecies coalescent methods that assume that different parts of the genome evolve at different rates. We found that the overall gene content, structure, and orientation are very conserved in all plastomes of the studied species. As observed in other Asteraceae, the 22 plastomes assembled here contain two nested inversions in the LSC region. The plastomes show similar length and the same gene content. The two most variable regions within Mikania are rpl32-ndhF and rpl16-rps3, while the three genes with the highest percentage of variable sites are ycf1, rpoA, and psbT. We generated six phylogenetic trees using concatenated maximum likelihood and multispecies coalescent methods and three data partitions: coding and non-coding sequences and both combined. All trees strongly support that the sampled Mikania species form a monophyletic group, which is further subdivided into three clades. The internal relationships within each clade are sensitive to the data partitioning and inference methods employed. The trees resulting from concatenated analysis are more similar among each other than to the correspondent tree generated with the same data partition but a different method. The multispecies coalescent analysis indicate a high level of incongruence between species and gene trees. The lack of resolution and congruence among trees can be explained by the sparse sampling (~ 0.45% of the currently accepted species) and by the low number of informative characters present in the sequences. Our study sheds light into the impact of data partitioning and methods over phylogenetic resolution and brings relevant information for the study of Mikania diversity and evolution, as well as for the Asteraceae family as a whole.